RF magnetron sputtered YSZ thin films: fabrication and characterization - Shahrul Razi bin Meskon (Kulliyyah of Engineering, International Islamic University Malaysia, 2011)
In order to obtain high ionic conductivity of a solid electrolyte at intermediate temperatures for intermediate-temperature solid oxide fuel cells (IT-SOFC), a very thin dense film is crucial due to its reduced ohmic losses. This work describes the fabrication of yttria-stabilized zirconia (8YSZ) thin films using radio frequency (RF) magnetron sputtering method. The thin films are deposited onto carbon paint coated stainless steel sheets with varying substrate temperature (Ts) of 150, 200, 250 and 300°C. Other sputtering parameters, i.e., argon gas flow rate, RF power and deposition time are fixed. The sputtering targets used are sintered YSZ pellets. Ultrathin YSZ films were successfully deposited with a thickness range of 300 to 600 nm as determined from the scanning electron microscopy (SEM). Phase composition analysis using X-ray diffraction (XRD) revealed cubic matrix with tetragonal and monoclinic crystalline phases of zirconia. Impedance spectroscopy (IS) is conducted at room temperature (RT) to measure the alternating-current (AC) total conductivity of the thin films. The conductivity increases with increasing substrate temperature Ts from 150°C to 250°C but drops slightly at Ts of 300°C. The highest room temperature AC total conductivity obtained is 1.81 x 10-6 Ω-1.cm-1 and the value is comparable with the reported direct-current (DC) bulk conductivity measured at a significantly higher temperature around 283°C.